Epidemiology and Outcome of Death Due to Burn Injuries –A Prospective Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
A burn is an injury which is caused by application of heat or chemical substances to the external or internal surfaces of the body, which causes destruction of tissues. Thermal deaths are those which result from the effects of systemic and/ or localized exposure to excessive heat and cold [1]. The present study has been carried out on 150(39 males and 111 females) cases of death due to burn, brought to the mortuary of Swaroop Rani Nehru Hospital, Moti Lal Nehru Medical College, Prayagraj for medico legal autopsy during the study period of one year extending from 01 July 2019 to 30 June 2020. Female outnumbered males i.e. 111(74.00%) females and 39(26.00%) males. Maximum number of burn deaths i.e., 56(37.33%) cases occurred in the young age group 21-30. Accidental burn injuries can be reduced by bringing about regulations to develop safer cooking appliances, promoting less inflammable fabrics to be worn at home and educating the community especially women.
Keywords: Burn; Mortuary; Thermal; Thermal Autopsy; Inflammable